2021
DOI: 10.3389/fnbot.2021.723206
|View full text |Cite
|
Sign up to set email alerts
|

Improved Physiological Gait in Acute and Chronic SCI Patients After Training With Wearable Cyborg Hybrid Assistive Limb

Abstract: In recent years robotic devices became part of rehabilitation offers for patients suffering from Spinal Cord Injury (SCI) and other diseases. Most scientific publications about such devices focus on functional outcome. The aim of this study was to verify whether an improvement in physiological gait can be demonstrated in addition to the functional parameters after treatment with neurological controlled HAL® Robot Suit. Fifteen subjects with acute (<12 months since injury, n = 5) or chronic (>12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Brinkemper et al. [8] reported that HAL walking rehabilitation promoted improvement of physiological gait in addition to functional improvement. They showed improvement in physiological parameters such as phases of the gait cycle and significant improvement in all spatiotemporal and gait phase parameters induced by HAL walking rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Brinkemper et al. [8] reported that HAL walking rehabilitation promoted improvement of physiological gait in addition to functional improvement. They showed improvement in physiological parameters such as phases of the gait cycle and significant improvement in all spatiotemporal and gait phase parameters induced by HAL walking rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other robots, movement occurs in response to the wearer’s voluntary drive. The effects of training with HAL as an intervention strategy to improve walking performance have been reported in patients with gait disorders of different etiologies for several years [ 17 , 18 , 19 , 20 , 21 ]. In adult patients with stroke and spinal cord injury, improvements in gait speed, step length, cadence, walking endurance, and functional parameters were shown [ 17 , 18 , 19 , 20 , 21 ]; however, HAL is not labeled for use for CP, and this remains investigational.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of training with HAL as an intervention strategy to improve walking performance have been reported in patients with gait disorders of different etiologies for several years [ 17 , 18 , 19 , 20 , 21 ]. In adult patients with stroke and spinal cord injury, improvements in gait speed, step length, cadence, walking endurance, and functional parameters were shown [ 17 , 18 , 19 , 20 , 21 ]; however, HAL is not labeled for use for CP, and this remains investigational. Even when a patient with CP can walk, if the patient continues to walk with an abnormal gait peculiar to CP, such as an equinus or crouching gait, the joints and soft tissues become very stressed.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of exoskeletal robotic technology can benefit the spinal cord injury population in three ways: (1) extensive repetitions of walking can help them improve and regain their walking ability, (2) the need for medical manual labor can be reduced, making extensive walking training feasible and even shortening the course of treatment, and (3) complications can be reduced, such as reduced pain, spasticity, osteoporosis and improved cardiorespiratory, lower urinary tract and bowel function (Esquenazi et al, 2012 ; Kolakowsky-Hayner, 2013 ; Benson et al, 2015 ; Stampacchia et al, 2016 ; Chun et al, 2019 ; Jang et al, 2019 ; Alashram et al, 2021 ; Brinkemper et al, 2021 ; Shackleton et al, 2021 ; Williams et al, 2021 ; Garnier-Villarreal et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%